Probiotics: Should We Consider it in Therapeutics? (Journal of Medicine, 2012)
Probiotics are receiving increasing attention in the medical field. This is partly due to the recognition that microbial resistance to antibiotics presents a serious world-wide problem. In addition, fast growing insight into host-microbe interactions opened new routes in the development of rational alternatives in therapy and prevention of diseases as result of the complex procaryotic-eucaryotic evolutionary symphony. Consequently, long existing aspects of probiotics came into focus, and already provide exciting prospects. DOI: http://dx.doi.org/10.3329/jom.v13i1.10049 JOM 2012; 13(1): 55-59